2021
DOI: 10.1109/tit.2020.3041650
|View full text |Cite
|
Sign up to set email alerts
|

Improved List-Decodability of Random Linear Binary Codes

Abstract: There has been a great deal of work establishing that random linear codes are as list-decodable as uniformly random codes, in the sense that a random linear binary code of rate 1 − H(p) − is (p, O(1/))-list-decodable with high probability. In this work, we show that such codes are (p, H(p)/ + 2)-list-decodable with high probability, for any p ∈ (0, 1/2) and > 0. In addition to improving the constant in known list-size bounds, our argument-which is quite simple-works simultaneously for all values of p, while pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(38 citation statements)
references
References 40 publications
(91 reference statements)
0
38
0
Order By: Relevance
“…The conjecture is known to be true over F 2 [10]. However, it is open in other cases if we insist the universal constant in the list size to be one.…”
Section: A Known Results For List Decoding Over Finite Fieldsmentioning
confidence: 94%
See 4 more Smart Citations
“…The conjecture is known to be true over F 2 [10]. However, it is open in other cases if we insist the universal constant in the list size to be one.…”
Section: A Known Results For List Decoding Over Finite Fieldsmentioning
confidence: 94%
“…Then by the continuity of the entropy function, the capacity is very low and can be a vanishing function of δ as δ Ñ 0. In this case, many existing list decodability results for 1 Actually, Li and Wootters [10] showed that for any constant γ ą 0, the list size of a random code is bounded from below by 1´γ δ whp. 2 Rigorously, there are two commonly used definitions of explicitness in the literature.…”
Section: A Known Results For List Decoding Over Finite Fieldsmentioning
confidence: 98%
See 3 more Smart Citations